Analysis of the Needs for Developing an Interactive Video-Based Learning Management System (LMS) in Physical Education Learning - Bagus Abdul Najid; Rajip Mustafillah Rusdiyanto (Educia Journal, 2026)
This study aimed to analyze the need for developing an interactive video-based Learning Management System (LMS) for Physical Education, Sports, and Health (PJOK) learning. The study used a quantitative descriptive design with survey and observation methods. The participants were 201 Grade VIII students, consisting of 98 males and 103 females aged 13 to 15 years, and one PJOK teacher. Data were collected using a student needs questionnaire and an observation sheet on school technology readiness. The questionnaire consisted of 18 items and showed excellent reliability with a Cronbach’s Alpha value of 0.980. Data were analyzed using descriptive percentage analysis, while observation data were interpreted descriptively. The findings showed that students had strong needs for flexible learning access, mobile-based learning materials, instructional videos, independent practice guidance, and more engaging PJOK learning experiences. The highest needs appeared in independent practice outside school, mobile accessibility, flexible learning access, and preference for engaging learning experiences. Observation results showed that the school had adequate technological infrastructure, including computers, LCD projectors, internet access, digital communication platforms, cameras, and audio systems. However, the use of technology in PJOK learning remained limited, especially in instructional videos, interactive applications, motion analysis tools, digital feedback, and LMS integration. These findings indicate a clear gap between available technological facilities and their use in PJOK instruction. Therefore, an interactive video-based LMS is relevant as a complementary learning system that supports teacher instruction, strengthens students’ independent practice, and improves learning flexibility in PJOK. Future development should prioritize simple, accessible, and practical first-stage features.